PROGRAM MAKAN BERGIZI GRATIS INDONESIA DALAM PANDANGAN MEDIA INTERNASIONAL BERBAHASA ARAB - Al Syarif, Said Muhammad Hasan (UI Scholars Hub, 2026)
This study examines how Indonesia’s Free Nutritious Meals (MBG) Program is represented in Arabic language media, focusing on the construction of ideology and the framing of public policy within discourse. As a quick-win initiative of President Prabowo Subianto’s administration in 2025, the MBG Program aims to improve nutrition and human capital quality, yet it has sparked controversy and drawn significant international media attention. This research addresses a gap in existing studies by critically analyzing the representation of Indonesian social policy in Arab media. The study employs a descriptive qualitative method using Norman Fairclough’s Critical Discourse Analysis (CDA), encompassing three dimensions: text, discourse practice, and social practice. The primary data consist of 25 online news articles in Arabic from the Middle East, North Africa, and Southeast Asia (January–October 2025). The analysis centers on two discourse orientations: pro (supportive) and contra (critical). The findings reveal a clear discursive dichotomy: 16 articles with a contra orientation highlight cases of mass food poisoning and implementation failures, while 9 pro-oriented articles frame the MBG Program as an ambitious, humanitarian initiative aligned with the “Golden Generation 2045” narrative. The CDA results underscore the role of Arab media as an instrument of symbolic diplomacy that constructs Indonesia’s image based on each outlet’s ideological stance and interpretive position.